Peranan Pemerintah Kelurahan dalam Penataan Lingkungan (Studi Tentang Pemasangan Ipal di Kelurahan Karya Jaya Kecamatan Kertapati Kota Palembang) - Irwansyah Irwansyah; Mega Nugraha; Alamsyah Alamsyah (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Irwansyah. The city of Palembang is one of the cities in Indonesia that has environmental problems, namely the existence of densely populated settlements in riverbank areas. With these conditions, the Palembang City Government has made efforts to prevent river water pollution as a form of Healthy City development. This is realized by the construction of a Wastewater Treatment Plant in Karya Jaya Village, Kertapati District, Palembang City, part of which is located right on the riverside. The main concern in this study is the role of the Government of Karya Jaya Village, Kertapati District, Palembang City in empowering the community to utilize communal WWTP which includes human empowerment, business empowerment, environmental empowerment, institutional empowerment, obstacles and efforts made to overcome them.The results of the study show that the role of the Karya Jaya Village Government, Kertapati District, Palembang City in environmental management consisting of human empowerment, business empowerment, environmental empowerment and institutional empowerment has not been carried out optimally. This is because the empowerment effort is a cross-sectoral effort. The obstacles that arise in the implementation of the role of the Karya Jaya Village Government, Kertapati District, Palembang City in environmental planning consist of budget limitations, community mindset and binding rules, which have not been overcome by the efforts that have been made, namely maximizing community participation and awareness. Therefore, the Government of Karya Jaya Village, Kertapati District, Palembang City should take coordination steps with related parties to maximize its role in environmental planning in the area. Thus, the environmental arrangement efforts carried out become more optimal and comprehensive. The Karya Jaya Village Government, Kertapati District, Palembang City should take intensive coordination steps with LPMK, RW, RT administrators, religious leaders and local community leaders to overcome various obstacles that arise in environmental planning in this region.